Italy at a turning point in its ecological research world (or not ?) (Avocetta, 2022)
A point of view from our Deputy Editor-in-Chief about whether the funds of the National Recovery and Resilience Plan (NRRP) have the potential to restore the Italian ecological research system. An hot-topic also for others EU countries.